Biomateriais xenogênicos ósseos não interferem na viabilidade e proliferação de células-tronco mesenquimais: estudo piloto - Stroparo, Jeferson Luis de Oliveira (2020)
The use of cells, especially mesenchymal stem cells (MSCs), is the subject of numerous researches, including tissue engineering. These cells are undifferentiated, presenting capacity for differentiation and self-renewal. They have the potential to transform into multiple cell types of the body, such as adipocytes, chondrocytes and osteoblasts, depending on the stimulus they receive. The main objective of this work was to evaluate, in an in vitro model, the influence of bovine xenogenic biomaterials on mesenchymal stem cells from human exfoliated deciduous teeth, in order to identify a biomaterial with higher potential cell carrier, for subsequent in vivo and/or clinical application. The following groups were used: 1) Control C (control), containing only MSCs; 2) Group BP, containing MSCs and Bonefill Porous® (0.60-1.50 mm); 3) Group BO, containing MSCs and Bios-Oss® (0.25-1 mm). The MSCs (P3) used came from a deciduous tooth in exfoliation from a 7-year-old male donor. A cell aliquot was submitted to immunophenotyping by flow cytometry. Cell viability (neutral red), cytotoxicity (TMT), and cell proliferation (violet crystal) tests were performed; all groups were submitted to morphological analysis by light microscopy (ML). Due to the results of previous tests, the biomaterial considered with superior performance was submitted to ultrastructural evaluation by scanning electron microscopy (SEM). The times of 24, 48 and 72 h of cultivation were used. Mesenchymal stem cell validation demonstrated positive surface markers for CD105, CD73, CD90, and negative for CD45, CD34, CD14, CD19, and HLA-DR. The results showed that both biomaterials maintained cell viability and cytotoxicity similar to group C. As for proliferation, there was a difference for less in the BO group compared to the other groups. To ML, the BP group presented more spread and adhered cells than the BO group. Thus, at SEM, the cells of the BP group presented characteristics of cells more active than those of group C, with secretion of vesicles to the extracellular matrix. Therefore, it can be concluded that BP presented a higher potential stem cell carrier for future studies with in vivo and/or clinical application.